The Influence Of Husband’s Support Towards The Case Of Menopause Syndrome Of Women In Sendangmulyo Village Tembalang Subdistrict Semarang City - Anisa Nur Jannah; Tinuk Istiarti; Anung Sugihantono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Background : The condition of life expectancy (UHH) of Indonesian people is 71 years old on the average, and WHO (World Health Organization) estimates that life expectancy of Indonesian people is 75 years old in 2025. As the result, there is an enhancement of elderly population so that many emerging health problems of elderly population rise simultaneously. Menopause syndrome is one kind of old women’s issue that needs to be prevented. Husband's support is one of some factors in the case of menopause syndrome suppression towards women. This research was carried out to find out the influence of husband’s support towards the case of menopause syndrome of women. Method: This study used descriptive analitic method and cross-sectional approach with the sample of 88 respondents of men with 45-54-year old menopausal wife selected by simple random sampling technique. The results obtained in this research were analyzed using univariate and bivariate analysis with a simple linear regression test (level of significance 0.05). Result: The result of simple linier regression test with independent variables showed two variables that influenced the case of menopause syndrome of women were respondents' knowledge about menopause (p≤0.05, p=0.0001) and respondents’ attitude (p≤0.05, p=0.017). Meanwhile, variables that didn’t affect the menopause syndrome case of women were the availability of information regarded to menopause (p>0.05, p=0.934) and the external support of themenopause (p>0.05, p=0.885). Conclusions: There are the influence of the respondents’ knowledge about menopause andrespondents’ attitude with the case of menopause syndrome suppression towards wife.